Mental Abuse Detection System Based on IoT - Khalid, Asmaa Khalidah; Yahya @ Atan, Roshayati (Evolution in Electrical and Electronic Engineering, 2023)
The challenges and pressures of modern life confront the younger generation until those who compete, putting them at risk of mental illness. Due to society’s unawareness that emotional abuse leaves deeper and could not be seen by the public eyes. Thus, this work is a system that can detect mental abuse specifically for youth. By referencing to symptoms of body temperature, heart rate, and oxygen saturation. By focusing on youth from 18 years old to 29 years old. The development of the system used of body temperature, oxygen saturation, and heart rate sensors to track the signs of an abnormal person using selected hardware and software of Node MCU ESP8266, MAX30100, MLX90614, Arduino IDE, and Blynk Application. This study shows that mental abuse can be detected by using the develop system with 98% of discrepancy and youth who are subjected to mental abuse can then be identified. Improving on GPS gives more accurate location and better monitoring the location of latitude and longitude in every second.